Perspective: Pragmatic Exercise Recommendations for Older Adults: The Case for Emphasizing Resistance Training - Tavoian, Dallin; Russ, David W.; Consitt, Leslie A.; Clark, Brian C. (Frontiers in Physiology, 2020)
Optimal health benefits from exercise are achieved by meeting both aerobic and muscle strengthening guidelines, however, most older adults do not exercise and the majority of those who do only perform one type of exercise. A pragmatic solution to this problem may be emphasizing a single exercise strategy that maximizes health benefits. The loss of muscle mass and strength at an accelerated rate are hallmarks of aging that, without intervention, eventually lead to physical disability and loss of independence. Additionally, older adults are at risk of developing several chronic diseases. As such, participating in activities that can maintain or increase muscle mass and strength, as well as decrease chronic disease risk, is essential for healthy aging. Unfortunately, there is a widely held belief that adaptations to aerobic and resistance exercise are independent of each other, requiring the participation of both types of exercise to achieve optimal health. However, we argue that this assertion is incorrect, and we discuss crossover adaptations of both aerobic and resistance exercise. Aerobic exercise can increase muscle mass and strength, though not consistently and may be limited to exercise that overloads a particular muscle group, such as stationary bicycling. In contrast, resistance exercise is effective at maintaining muscle health with increasing age, and also has significant effects on cardiovascular disease risk factors, type 2 diabetes, cancer, and mortality. We posit that resistance exercise is the most effective standalone exercise strategy for improving overall health in older adults and should be emphasized in future guidelines.